Recovery rate and predictors among children aged 6–59 months with severe acute malnutrition in Addis Ababa, Ethiopia: a retrospective follow-up study - Getahun, Genanew Kassie; Andabo, Wondimu Ayele; Shewamare, Abraham; Birhanu, Molla Yigzaw (Frontiers in Pediatrics, 2024)
Introduction Severe acute malnutrition (SAM) is a critical public health concern in Ethiopia, contributing to high morbidity and mortality rates among children. Despite the improvement in hospital coverage and the development of standardized WHO treatment guidelines, recent reviews indicated a wide range in recovery rates (34%–88%) due to several context-specific factors. Understanding the factors influencing the recovery time can help inform targeted interventions and improve the overall management of SAM cases. Therefore, this study aimed to assess the time to recovery and predictors of children aged 6–59 months with severe acute malnutrition in Addis Ababa, Ethiopia, in 2023. Methods An institutional-based retrospective follow-up study was conducted among children aged 6–59 months who were admitted to Tirunesh Beijing Hospital (TBH), Addis Ababa, Ethiopia, from July 2019 to June 2023. The Kaplan–Meir estimate and survival curve were used to compare the time to recovery using a log-rank test among different characteristics. A Cox proportional hazard regression analysis model was used to identify significant predictors of time to recovery. Finally, a p-value of <0.05 was used to declare a significant association. Results The median survival time to recovery was 17 (95% CI: 16.39–17.60) days, and the incidence rate of recovery from SAM was 37.8 per 1,000 child days. Moreover, exclusive breastfeeding [adjusted hazard ratio (aHR): 1.97, 95% CI: 1.45–2.68], amoxicillin provision (aHR = 1.62, 95% CI: 1.11–2.35), and deworming (aHR = 2.14, 95% CI: 1.48–3.09) were protective factors. However, complications at admission (aHR = 0.41, 95% CI: 0.23–0.73) and diarrhea during admission (aHR = 0.64, 95% CI: 0.45–0.91) were identified as risk factors of recovery from SAM. Conclusion The time to recovery among the current study participants was low compared with the sphere standard. Besides, exclusive breastfeeding, complications at admission, diarrhea, amoxicillin provision, and deworming were independent predictors. Therefore, appropriate provision of routine medication and early management of medical comorbidity as per the national SAM management protocol can reduce the mortality of children with severe acute malnutrition significantly.